Optimalisasi Mutu Pelayanan Rekam Medis melalui Edukasi, Pelatihan, Pendampingan, dan Implementasi Sistem Informasi Manajemen Klinik bagi Petugas PMB Jurusan Kebidanan Poltekkes Kemenkes Yogyakarta : Optimizing Medical Record Service Quality through Education, Training, Mentoring, and Implementation of a Clinic Management Information System for Staff at the Independent Midwifery Practice (PMB), Department of Midwifery, Poltekkes Kemenkes Yogyakarta - Arif Nugroho Triutomo; Nita Budiyanti; Hari Wibowo; Syarah Mazaya Fitriana (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2025)
Quality medical record services are an important component in supporting the efficiency and quality of healthcare delivery. A preliminary assessment at the Independent Midwifery Practice (PMB), Department of Midwifery, Poltekkes Kemenkes Yogyakarta, identified several problems, including the continued use of manual medical record documentation, suboptimal utilization of computers, relatively long registration service times, and limited storage capacity for medical record documents. This community service program aimed to improve staff knowledge and competency regarding Electronic Medical Records (EMR) through education, training, mentoring, and implementation of a Clinic Management Information System (SiKlik), while improving the quality of registration services. The program was conducted from March to October 2024 using a blended approach and involved 12 staff members at the Independent Midwifery Practice (PMB), Department of Midwifery, Poltekkes Kemenkes Yogyakarta. The activities included EMR education, demonstration and hands-on practice in using SiKlik, mentoring during system implementation in the registration process, and evaluation using pretest and posttest assessments. Service quality was evaluated through a satisfaction survey involving 30 patients who had received services before and after EMR implementation. The results showed that the mean staff knowledge score increased by 24 points, from 65 at pretest to 89 at posttest. All participants (100%) were able to operate the basic functions of SiKlik, and system utilization in daily services reached 100%. The implementation of SiKlik also improved registration service efficiency, with the mean service time decreasing from 35 minutes to 15 minutes. All patients (100%) reported that the service was faster, and overall patient satisfaction reached 100%. The education, training, mentoring, and implementation of SiKlik demonstrated positive outcomes in improving staff competency, service efficiency, and patient satisfaction. The implementation of a Clinic Management Information System can support the transition from manual to electronic medical records and contribute to improving the quality of services at the Independent Midwifery Practice (PMB), Department of Midwifery, Poltekkes Kemenkes Yogyakarta.